(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تمت، في هذا العمل، معايرة المميزات التجريبية لكاشف NaI(Tl) ودراستها، حيث تم تحديد الجهد الأمثل المطبق على الكاشف السابق من أجل الطاقتين 662keV (طاقة أشعة غاما الناتجة عن نظير السيزيوم 137) و 1460keV (طاقة أشعة غاما الناتجة عن نظير البوتاسيوم 40)، وكذلك تحديد مقدرتي الفصل للكاشف السابق بالنسبة للطاقتين السابقتين. كما تمَّ رسم مستقيم معايرة الطاقة للكاشف أعلاه. وباستخدام طريقة المعايرة أعلاه، تمت دراسة ظهور أثر الخلفية في عينة من ماء الشرب المستعمل في مدينة اللاذقية. Calibration, the experimental of characteristics of a NaI(Tl) – detector, and the best voltage value of it, were determined for the 662 keV energy (g - energy resulted from Cs-137) and 1460 keV energy (g - energy resulted from potassium - 40) isotopes. Energy calibration straight - line of the detector has been obtained. Background effect and its apparition in Lattakia – drinking – water, was also studied. The result proved that there in no radioactive sources in that water.